Modulation of Host Immune Response Is an Alternative Strategy to Combat SARS-CoV-2 Pathogenesis - Singh, Lakhveer; Bajaj, Sakshi; Gadewar, Manoj; Verma, Nitin; Ansari, Mohd Nazam; Saeedan, Abdulaziz S.; Kaithwas, Gaurav; Singh, Manjari (Frontiers in Immunology, 2021)
The novel SARS-CoV-2 caused the disease COVID-19, is currently a pandemic worldwide. The virus requires an alveolar type-2pneumocyte host to initiate its life cycle. Viral S1spike protein helps in the attachment of virus on ACE-2 receptors present on type-2 pneumocytes, and S2 spike protein helps in the fusion of viral membrane with the host membrane. Fusion of SARS-CoV2 virus and host membrane is followed by transfer of viral RNA into the host cells which is directly translated into viral genome and a viral structural protein. As the virus replicates within type-2 pneumocytes, the host immune system is activated, and alveolar macrophages start secreting cytokines and chemokines, acting as an inflammatory mediator and chemotactic neutrophils, monocytes, natural NK cells, and CD8+ T cells that initiate local phagocytosis of infected cells. It’s not the virus that kills COVID-19 patients; instead, the aberrant host immune response kills them. Modifying the response from the host immune system could reduce the high mortality due to SARS-CoV-2 infection. The present study examines the viral life cycle in type 2pneumocytes and resultant host immune response along with possible therapeutic targets.